Maharashtra State BoardHSC Arts 12th Board Exam
Advertisement Remove all ads

In ΔABC, prove that b2-c2acosA+c2-a2bcosb+a2-b2ccosC = 0 - Mathematics and Statistics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

In ΔABC, prove that `("b"^2 - "c"^2)/"a" cos"A" + ("c"^2 - "a"^2)/"b" cos"B" + ("a"^2 - "b"^2)/"c" cos "C"` = 0

Advertisement Remove all ads

Solution

In ΔABC by cosine rule, we have

cos A = `("b"^2 + "c"^2 - "a"^2)/(2"bc")`, cosB = `("a"^2 + "c"^2 - "b"^2)/(2"ac")`, cos C = `("a"^2 + "b"^2 - "c"^2)/(2"ab")`

∴ L.H.S. = `("b"^2 - "c"^2)/"a" cos"A" + ("c"^2 - "a"^2)/"b" cos"B" + ("a"^2 - "b"^2)/"c" cos "C"`

= `("b"^2 - "c"^2)/"a" xx ("b"^2 + "c"^2 - "a"^2)/(2"bc") + ("c"^2 - "a"^2)/"b" xx ("a"^2 + "c"^2 - "b"^2)/(2"ac") + ("a"^2 - "b"^2)/"c" xx ("a"^2 + "b"^2 - "c"^2)/(2"ab")`

= `1/(2"abc") ("b"^4 + "b"^2"c"^2 - "a"^2"b"^2 - "b"^2"c"^2 - "c"^4 + "a"^2"c"^2 + "a"^2"c"^2 + "c"^4 - "b"^2"c"^2 - "a"^4 - "a"^2"c"^2 + "a"^2"b"^2 + "a"^4 + "a"^2"b"^2 - "b"^4 + "b"^2"c"^2)` 

= 0

= R.H.S

Concept: Solutions of Triangle
  Is there an error in this question or solution?
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×